PENGARUH MANAJEMEN PERPUSTAKAAN TERHADAP MINAT BACA PESERTA DIDIK KELAS XI DIMAS MA’ARIF LASEPANG KAB. BANTAENG - Rasyid, Muhammad Rusydi; Nurul Ainun P (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
This research aims to determine the effect of library management on reading interest in class XI students at MAS Ma'arif Lasepang Kab. Bantaeng. The formulation of the problem in this study is how the influence of class XI library management at MAS Ma'arif Lasepang Kab. Bantaeng, How is the Reading Interest of Class XI Students at MAS Ma'arif Lasepang Kab. Bantaeng, How is the Influence of Library Management on the Reading Interest of Class XI Students at MAS Ma'arif Lasepang Kab. bantaeng. The method used in this research is quantitative which expects scientists to go directly to the field. The population in this review are all students of class XI MAS Ma'arif Lasepang Kab. Bantaeng 48 students. The test method is a saturated sample where all individuals from the population are used as a test. The various information instruments used are questionnaires and Documentation. The information is then broken down descriptively and inferentially. The results of the study in this study were the influence of library management and reading interest in class XI students at MAS Ma'arif Lasepang Kab. bantaeng. Based on the results of the simple regression test, a significance value of 0.000 was obtained. The significance value obtained is smaller than (0.000 < 0.05). So it can be concluded that there is an influence of library management and reading interest of class XI students at MAS Ma'arif Lasepang Kab. bantaeng. The results of the T test using SPSS showed that Thit = 9.321 > Ttable = 2.014, so it can be concluded that there is an influence of library management and reading interest in class XI students at MAS Ma'arif Lasepang Kab. Bantaeng.